2004
DOI: 10.1007/bf02968003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the metal clip in a breast: safety ana its availability as a negative marker

Abstract: The safety and reliability of breast MR examination using a mammotome clip was demonstrated by both the mock examination and the breast examination. It is possible to localize of tumor spread regions based on the marker position using the clip as a negative signal marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Metallic clips are stable in the 1.5 and 3 T MRI environment [53], not associated with substantial heating despite high-radiofrequency exposure [54].…”
Section: Biopsy Clips and The Mri Environmentmentioning
confidence: 99%
“…Metallic clips are stable in the 1.5 and 3 T MRI environment [53], not associated with substantial heating despite high-radiofrequency exposure [54].…”
Section: Biopsy Clips and The Mri Environmentmentioning
confidence: 99%
“…In the present study, a newly developed, metallic tissue marker underwent MRI testing using standardized test procedures in consideration of current clinical MR systems, insofar as 3 Tesla was utilized for the assessment of magnetic field interactions and a relatively high, whole body averaged SAR level was applied during the heating evaluation. While other tissue markers have undergone MRI testing [ 6 , 8 , 20 22 ], to our knowledge, the evaluation of several of these markers did not follow the accepted standardized tests as recommended by the United States Food and Drug Administration (i.e., following the documents from the ASTM International) [ 23 ]. Therefore, the relative risks of using MRI in patients with those particular tissue markers are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an investigation by Genson et al [ 20 ] assessed a range of tissue markers and found that these markers created signal voids that were two to six times the diameter of the marker, which is potentially problematic because subsequent lesion detection may be compromised if the extent of the artifact is too extensive. Because of the low magnetic susceptibility value for gold [ 24 ], which is lower than the other materials that have been previously used for metallic markers, this new marker appears to be ideally suited for MRI applications where the extent of the artifact is an important consideration [ 6 , 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hierbei sind Fälle beschrieben, die bis in Höhe der Hautinzision disloziert waren [25,26]. Als weitere Limitationen der Clipmarkierung sind zum einen der erhebliche Kostenaufwand und zum anderen das Problem der Maskierung der Lä-sion durch das Artefakt des Clips zu nennen [25,27].…”
Section: Markierung In Bauchlageunclassified